Potential consequences of post-Brexit trade barriers for earnings inequality in the UK - Rachel Griffith; Peter Levell; Agnes Norris Keiller (Institute for Fiscal Studies (IFS), 2020)
We examine the distributional consequences of post-Brexit trade barriers on wages in the UK. We quantify changes in trade costs across industries accounting for input-output links across domestic industries and global value chains. We allow for demand substitution by firms and consumers and worker reallocation across industries. We document the impact at the individual and household level. Blue-collar workers are the most exposed to negative consequences of higher trade costs, because they are more likely to be employed in industries that face increases in trade costs, and are less likely to have good alternative employment opportunities available in their local labour markets. Overall new trade costs have a regressive impact with lower-paid workers facing higher exposure than higher-paid workers once we account for the exposure of other household members.
Keywords: D33; D57; F61; F66; J20; 330; Trade; income distribution; inequality